2015
DOI: 10.1007/s11595-015-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior and failure mechanism of recycled semi-flexible pavement material

Abstract: The mechanical behavior and failure mechanism of recycled semi-flexible pavement material were investigated by different scales method. The macroscopic mechanical behavior of samples was studied by static and dynamic splitting tensile tests on mechanics testing system (MTS). The mechanical analysis in micro scale was carried out by material image analysis method and finite element analysis system. The strains of recycled semi-flexible pavement material on samples surface and in each phase materials were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Therefore, these methods need further investigation and selection to uncover properties of GSP concisely. Further, Ding et al, investigated recycled Semi-flexible Pavement material by splitting test at 20 • C, which indicated its anti-cracking resistance was positively linked with viscoelasticity of the binder [109].…”
Section: Low-temperature Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these methods need further investigation and selection to uncover properties of GSP concisely. Further, Ding et al, investigated recycled Semi-flexible Pavement material by splitting test at 20 • C, which indicated its anti-cracking resistance was positively linked with viscoelasticity of the binder [109].…”
Section: Low-temperature Performancementioning
confidence: 99%
“…Similarly, in another test, Ding et al, considered different factors from Ling: the intermittent time coefficient was 7; the crack propagation coefficient was 20; the Days number of the unfavorable season was 60; and the transverse distribution coefficient was 0.5. The result was expressed as follows [109]: [117,118]. Due to an additional factor of 1.1 for the lateral load distribution, 45 was finally determined as the correction factor [117,118].…”
Section: Fatigue Correction Factormentioning
confidence: 99%
“…In order to improve the material and structure for crack resistance, it is necessary to judge the weak position of the SFP mixture and the crack control stress. In order to find the weak parts, Ding built a SFP finite element model through digital image processing technology, characterized the distribution of materials through three-phase material structure, inferred the weak points of materials in cracks through tensile strain, and considered that the probability of cracks appearing at the interface between asphalt and grouting materials was greater [12]. A. Setyawan believes that the strength of SFP mainly depends on the strength of cement binder, and the compressive strength of cold mix grouting composite is lower than that of hot mix grouting material [13].…”
Section: Introductionmentioning
confidence: 99%
“…e failure possibility order of each phase in recycled semiflexible pavement material was asphalt binder, reclaimed aggregate, cement paste, and virgin aggregate [16]. Yang and Weng revealed that the void content of porous asphalt mixture is the most important factor influencing the durability of SFP subjected to cyclic wheel load [17].…”
Section: Introductionmentioning
confidence: 99%